Public Support for E-Cigarette-related Policies among a Nationally Representative Sample of US Adults. (September 2020) - Czaplicki, Lauren; Simpson, Randall; Zhou, Yitong; Patel, Minal; Cuccia, Alison F.; Vallone, Donna M.; Schillo, Barbara A.
Background: The wide availability of flavored e-cigarettes and broad use of e-cigarettes in public places may contribute to the rapidly increasing rates of use among youth and young adults in the U.S. However, policies at the federal, state and local levels can address these factors. Objective: Assess public support for 5 e-cigarette-related policies and evaluate response patterns by demographics, tobacco use, e-cigarette harm perceptions, geographic region, and strength of state-level clean indoor air policies. Methods: Data were collected Oct-Dec 2018 from a nationally representative online panel of U.S. adults (n = 3211). We measured support for 5 policies: (1) a ban on the sale flavored e-cigarettes; (2) requiring tobacco products, like e-cigarettes, be kept out of view in stores where adolescents shop; and prohibiting e-cigarette use in (3) all public places; (4) restaurants; and (5) bars. Weighted, adjusted logistic regressions modeled variation in policy support. Results: A majority of respondents (63.3%) supported a flavor ban, with no differences in support by smoking status. Most respondents supported keeping tobacco products out of view (78.0%) and prohibiting e-cigarette use in indoor public places (82.9%), restaurants (86.5%), and bars (76.1%). In the adjusted models, current e-cigarette users had significantly lower odds of policy support compared to never users. We observed no differences in support by geographic region or strength of state-level clean indoor air policies. Conclusion: Results suggest high levels of public support to regulate e-cigarette flavors, marketing, and use in public places. Targeted messaging may be needed to increase support among current e-cigarette users.